Higher minor hemoglobin A2 levels in multiple sclerosis patients correlate with lesser disease severity - Ozcan ME (Dove Medical Press, 2016)
Muhammed Emin Ozcan,1 Bahri Ince,2 Hasan Huseyin Karadeli,3 Asuman Gedikbasi,4 Talip Asil,3 Meric A Altinoz5 1Department of Neurology, Biruni University, 2Centre for Mood Disorders, Bakirkoy Research and Training Hospital for Psychiatry, 3Department of Neurology, Bezmialem University, 4Department of Biochemistry, Sadi Konuk Bakirkoy State Hospital, 5Department of Immunology, Experimental Medicine Research Institute (DETAE), Istanbul University, Istanbul, Turkey Objective: To define whether minor adult hemoglobin A2 (HbA2, α2δ2) exerts any protective activity in multiple sclerosis (MS). Methods: HbA2 levels were measured in 146 MS patients with high performance liquid chromatography and association with MS Severity Scores (MSSS) were determined. HbA2 associations with blood count parameters were also studied using blood counts evaluated on the same day of high performance liquid chromatography sampling. Routine biochemical parameters were also determined to rule out elusively influential factors, such as anemia and thyroid disorders. Results: HbA2 levels negatively correlated with MSSS (Spearman correlation, R: -0.186, P=0.025). Exclusion of confounding factors with a generalized linear model revealed an even stronger negative correlation between HbA2 and MSSS (P<0.001). HbA2 positively correlated with red blood cells (RBCs) (R=0.350, P<0.001) and in turn, RBCs negatively correlated with MSSS (R=-0.180, P=0.031). Average HbA2 levels were highest among patients treated with interferon β1a. Conclusion: RBC fragility is increased in MS, and recent data suggest that circulating free Hb contributes to neural injury in MS. HbA2 and its oxidative denaturation product hemichrome A2 enhance RBC membrane stability to a greater extent than do major HbA or hemichrome A. Reductions in ischemic cerebrovascular vascular events are reported in β-thalassemia carriers and HbA2 levels are considerably higher in this population. Episodic declines of cerebral blood flow were shown in bipolar disorder, and we have recently shown a protective role of HbA2 against postpartum episodes in females with bipolar disorder. HbA2’s erythroprotective functions may reduce free Hb and long-term neural injury in MS. Keywords: multiple sclerosis, erythrocytes, adult minor hemoglobin, hemoglobin A2